Minat Masyarakat Muslim terhadap Jasa Bank Syariah Perspektif Bank Syariah dan Perilaku Masyarakat - Muarif, Ahmad Dalhar; Wakhrodi, Wakhrodi (Fakultas Syariah dan Ekonomi Islam Institut Pesantren Mathali'ul Falah, 2024)
Indonesia is an ideal market for Islamic banking because the majority of the population is Muslim. Only 6.63% of the total national banking assets were owned by Islamic banks in Indonesia in 2022. This shows that people are not too interested in using Islamic bank services. This research is qualitative research that uses a case study approach. Data collected from interviews with a hundred randomly selected people. The purpose of this study is to determine the level of public demand for Islamic banks based on the perspective of Islamic banks (marketing mix) and community behavior. The results of the study show that factors related to Islamic banks include the lack of office networks and promotions that make Muslims not use their services. In addition, personal and social factors are also the most important factors in influencing people's behavior. The study recommends Islamic banks to create marketing policies that are appropriate to the Muslim community.